2012
DOI: 10.1111/j.1471-6712.2012.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Taiwanese long‐term care facility residents' experiences of caring: a qualitative study

Abstract: The findings of this study confirm the need for managers of LTCFs to address the physical and psychosocial needs of their residents. The findings can be used to develop education programmes and clinical protocols for nurses in the caring field and to develop instruments for measuring perceived caring in LTCFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 33 publications
5
60
0
Order By: Relevance
“…Recognizing the need for social interaction by residents can facilitate caring behaviors (Bedin et al, 2013). For example, our previous study (Hwang et al, 2013) revealed the importance of relational activities for caregivers and residents.…”
Section: Consequences Of Caringmentioning
confidence: 99%
See 3 more Smart Citations
“…Recognizing the need for social interaction by residents can facilitate caring behaviors (Bedin et al, 2013). For example, our previous study (Hwang et al, 2013) revealed the importance of relational activities for caregivers and residents.…”
Section: Consequences Of Caringmentioning
confidence: 99%
“…Being sensitive is a foundation of caring that requires going beyond routine nursing practices. That is, the care worker must be emotionally open and available (Bedin et al, 2013) and must be active rather than passive when meeting people or speaking with people (Hwang et al, 2013;Wilkin & Slevin, 2004). In other studies, for example, categories or factors that support this caring attribute have been coded as showing respect, empathy, encouragement, or expression (de Guzman et al, 2012;Hwang et al, 2013;Liu, 2004;Papastavrou et al, 2011;Wolf et al, 2006), applying a person-centered approach to care instead of a taskcentered approach (Tuckett et al, 2009), understanding without complaining (Hwang et al, 2013), and being available for relationship building (Kubiak & Sandberg, 2011).…”
Section: Seeingmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the trace of other dimensions of care is somehow observed, it is based on common sense and personal experiences (7). Research showed that in Taiwan and Hong Kong, the main concerns of the older people concerning care in nursing homes were about loneliness, physical misbehavior, social isolation and inadequacy of self-care and decision making (8). In this direction, existence of physical and psychological misbehavior, neglect and low quality of care is also notable (6).…”
Section: Introductionmentioning
confidence: 99%